2014
DOI: 10.1074/jbc.m114.616466
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Interaction That Is Essential for the Biogenesis of Histone Locus Bodies

Abstract: Background: Proteins involved in expression of histone genes co-localize to discrete nuclear structures called histone locus bodies (HLBs). Results: Two main components of HLBs directly interact with each other through their C-terminal regions. Conclusion: Formation of HLBs depends on a subset of critical protein-protein interactions. Significance: Our work may help to understand the mechanisms that integrate transcription of histone genes with maturation of the nascent histone transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 71 publications
4
65
0
Order By: Relevance
“…We recently demonstrated that the C-terminal domain of FLASH directly interacts with the last 25 amino acids of NPAT [24]. Interestingly, a homologous SANT/Myb-like domain capable of interacting with the same region of NPAT also exists at the end of the unrelated vertebrate protein Yin Yang 1-associated protein-related protein (YARP).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that the C-terminal domain of FLASH directly interacts with the last 25 amino acids of NPAT [24]. Interestingly, a homologous SANT/Myb-like domain capable of interacting with the same region of NPAT also exists at the end of the unrelated vertebrate protein Yin Yang 1-associated protein-related protein (YARP).…”
Section: Introductionmentioning
confidence: 99%
“…with »500,000 for U1 snRNA in mammals) and very small amounts of FLASH in Drosophila embryos and larvae. 72 FLASH is recruited to the HLB by an interaction between the C-terminus of FLASH and the C-terminus of NPAT/Mxc 29,44,72,73 . A hypomorphic allele of mxc (mxc G46 ) that encodes a truncated form of Mxc lacking the last 195 amino acids results in failure of full length, wild type FLASH protein and U7 snRNP to concentrate in the HLB, although an HLB containing the truncated Mxc protein forms.…”
Section: Hlb Functionmentioning
confidence: 99%
“…42 A second example is muscle wasted (Mute), discovered by the Chia lab in a screen for factors required for muscle development and shown to concentrate in the HLB, 43 as does its mammalian ortholog YARP. 44 Mute may function as a negative regulator of histone gene expression. 43 Dominski and colleagues also showed that cleavage of histone pre-mRNA is catalyzed by CPSF-73, the same protein that catalyzes cleavage of pre-mRNAs encoding poly(A) mRNAs, demonstrating a role for polyadenylation factors in histone pre-mRNA processing, 45 including Symplekin 46 and CPSF100.…”
Section: An Expanding List Of Hlb Componentsmentioning
confidence: 99%
See 2 more Smart Citations